2007
DOI: 10.1590/s0034-89102007000600012
|View full text |Cite
|
Sign up to set email alerts
|

Violência contra a mulher, coesão familiar e drogas

Abstract: OBJECTIVE:To evaluate the association between cohesion, adaptability and mental risk in families, physical violence against women and the use of drugs. METHODS:Data for this paired case-control study was collected in 2004 and 2005 in the city of Joao Pessoa, in Northeastern Brazil. The sample included 260 women, divided into 130 battered individuals and 130 non-battered. The case study group consisted of women who lodged complaints for domestic violence at the Specialist Women's Police Station. The control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
38

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 12 publications
1
8
0
38
Order By: Relevance
“…Several studies have found a higher consumption of licit and illicit drugs in families where there is violence towards women or when the offender uses alcohol and drugs [26][27][28] , characterizing alcohol consumption as a risk factor for violence against women. The relationship between alcohol consumption and crime is recognized as a serious social and public health issue, because alcohol, due to pharmacological stimulation, acts as a releasing factor for aggression, and has been used as justification for abusive behavior by both the perpetrators and the professionals and institutions 28,29 . However, in recent years, researchers have criticized the causal attribution of violence to addictive behaviors such as alcohol and drugs, showing that it can minimize the sociocultural character of violence 17,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found a higher consumption of licit and illicit drugs in families where there is violence towards women or when the offender uses alcohol and drugs [26][27][28] , characterizing alcohol consumption as a risk factor for violence against women. The relationship between alcohol consumption and crime is recognized as a serious social and public health issue, because alcohol, due to pharmacological stimulation, acts as a releasing factor for aggression, and has been used as justification for abusive behavior by both the perpetrators and the professionals and institutions 28,29 . However, in recent years, researchers have criticized the causal attribution of violence to addictive behaviors such as alcohol and drugs, showing that it can minimize the sociocultural character of violence 17,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, verificam-se altos índices de violência familiar entre a população usuária de drogas, o que também pode ser desencadeante de separações frequentes (Bonifaz & Nakano, 2004;Rabello & Caldas Júnior, 2007).…”
Section: Discussionunclassified
“…The consumption of alcoholic drinks by the partners is one of the main causes leading the partner to commit crime. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Attention is also called to the fact that the women state that the use of drugs/alcohol is the event causing conjugal violence, it being considered that if this is absent, the conjugal relationship is healthier. The women studied declared that when their partners drink, they are transformed, attacking them, initially verbally, and then progressing to other types of violence.…”
mentioning
confidence: 99%